Low-VOC and high-conductivity thermoplastic resin composite material and preparation method thereof

By using doped mesoporous magnesium oxide/polyaniline composite materials as functional fillers in thermoplastic resin composites, the problem of insufficient VOC performance and conductivity of existing materials is solved, and better VOC performance and conductivity are achieved. Expanded the application areas of materials.

CN119431944APending Publication Date: 2025-02-14HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310951024.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing thermoplastic resin composites have insufficient VOC performance and conductivity in automotive interiors and automotive electronic systems, which limits their application areas.

Method used

Doped mesoporous magnesium oxide/polyaniline composite material is used as functional filler to adsorb VOC through mesoporous magnesium oxide and form a conductive network with polyaniline to improve the VOC and conductivity of the material.

Benefits of technology

The VOC performance and electrical conductivity of thermoplastic resin composites are significantly improved, the emission of pollutants is reduced, and the surface resistivity of the material is lower than that of the composite materials using conventional conductive agents in the comparative examples.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a low-VOC (volatile organic compound) and high-conductivity thermoplastic resin composite material and a preparation method thereof. The thermoplastic resin composite material consists of the following components in parts by weight: 90-110 parts of thermoplastic resin, 10-16 parts of functional filler and 0.1-0.5 part of antioxidant, the functional filler is a doped mesoporous magnesium oxide / polyaniline composite material. The functional filler is adopted to modify the thermoplastic resin, so that small molecular substances in VOC can be adsorbed, and the VOC performance of the thermoplastic resin composite material is improved. The formation of a polyaniline gel conductive network structure can be promoted, and the conductivity of the thermoplastic resin composite material is enhanced. The material can be used in the fields of automobile and household appliance materials, and has excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a thermoplastic resin composite material with excellent VOC performance and good electrical conductivity and a preparation method thereof. Background Art

[0002] Thermoplastic resin is a widely used polymer polyester resin. Thermoplastic resin has the advantages of good fatigue resistance, good heat resistance and excellent dimensional stability. However, in some specific automotive material application fields, the VOC performance and conductive properties of thermoplastic resin are very high, which limits the application of thermoplastic resin composites in some specific fields.

[0003] If used in automotive interior parts, there are certain restrictions on the VOC emissions of thermoplastic resins. For example, GB / T27630-2011 Passenger Car Air Quality Requirements requires VOC content ≤ 300ug / m 3 . If used in automotive electronic systems, the conductivity of thermoplastic resins is required to be high. For example, in electronic connectors, sensors and electric drive systems, thermoplastic resins need to have good conductivity to ensure the transmission of electrical signals and the normal operation of circuits. The conductivity requirements usually involve the material's volume resistance, surface resistance and electromagnetic shielding. Generally, the surface resistivity of the material is required to reach 10 6 Ω. Currently, this is mainly achieved by adding conductive agents such as carbon black, but the surface resistivity of the final material reaches 10 7 Ω, higher than the requirement.

[0004] In view of these deficiencies, the present invention innovatively synthesizes a thermoplastic resin composite material with excellent VOC performance and good electrical conductivity. This thermoplastic resin composite material has good VOC performance and electrical conductivity. This thermoplastic resin composite material has not been reported so far, which has very important practical significance for expanding the application field of thermoplastic resin composite materials. Summary of the invention

[0005] In view of this, the present invention innovatively synthesizes a thermoplastic resin composite material with excellent VOC performance and good electrical conductivity, which has good electrical conductivity and VOC performance, and solves the technical problems of limited VOC performance and electrical conductivity of thermoplastic resins in the prior art.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A low-VOC, high-conductivity thermoplastic resin composite material, comprising the following components in parts by weight:

[0008] Thermoplastic resin 90-110 parts

[0009] Functional filler 10-16 parts

[0010] Antioxidant 0.1-0.5 parts

[0011] The functional filler is a doped mesoporous magnesium oxide / polyaniline composite material.

[0012] In a further embodiment, the preparation method of the doped mesoporous magnesium oxide / polyaniline composite material is as follows:

[0013] (1) placing mesoporous magnesium oxide, an initiator, a dopant, aniline, and aminotri(methylenephosphonic acid) in deionized water and reacting them in a water bath;

[0014] (2) The reaction solution is filtered, washed and dried to obtain a doped mesoporous magnesium oxide / polyaniline composite material.

[0015] In a preferred embodiment, the initiator is sodium persulfate, benzoyl peroxide or azobisisobutyronitrile, and the dopant is antimony hexafluoride, arsenic pentafluoride or silicon tetrafluoride.

[0016] In a preferred embodiment, the mass ratio of the mesoporous magnesium oxide, the initiator, the dopant, the aniline and the aminotri(methylenephosphonic acid) is (30-40): (0.3-0.5): (0.1-0.3): (40-48): (30-50).

[0017] In a preferred embodiment, the reaction in a water bath condition refers to reacting in a water bath at 70-90° C. for 10-16 hours; and drying refers to drying in a drying oven at 50-70° C. for 40-48 hours.

[0018] In a further embodiment, the preparation method of the mesoporous magnesium oxide is as follows:

[0019] (1) adding a magnesium chloride aqueous solution to a sodium oxalate solution and reacting in a water bath;

[0020] (2) filtering the reaction solution, washing, and drying to obtain a solid substance;

[0021] (3) The solid material is placed in a muffle furnace and calcined to obtain mesoporous magnesium oxide.

[0022] The reaction equation is as follows:

[0023] 2NaC2O4+MgCl2→2NaCl+MgC2O4

[0024] 2MgC2O4+O2→2MgO+2CO2

[0025] In a preferred embodiment, the mass ratio of sodium oxalate to magnesium chloride is (30-40): (28-32);

[0026] The reaction in a water bath refers to reacting in a water bath at 60-80° C. for 12-16 hours;

[0027] The drying refers to drying in a drying oven at 60-80° C. for 10-12 hours, and the calcining refers to calcining at 680-720° C. for 8-12 hours.

[0028] In a further embodiment, the antioxidant is one or a mixture of tris(2,4-di-tert-butyl)phenyl phosphite (referred to as Irganox 168), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (referred to as Irganox 1010) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (referred to as Irganox 1330).

[0029] In a further embodiment, the thermoplastic resin is one of polyethylene (PE), polypropylene (PP), polystyrene (PS), polybutylene terephthalate (PBT), and polyamide 6 (PA6).

[0030] The second object of the present invention is to provide a method for preparing the above-mentioned thermoplastic resin composite material, which comprises the following steps:

[0031] (1) Weigh 90-110 parts of thermoplastic resin, 10-16 parts of functional filler, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture;

[0032] (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The mesoporous magnesium oxide contained in the functional filler of the present invention has the following functions: ① The mesoporous magnesium oxide can adsorb small molecules in VOC, thereby improving the VOC performance of the thermoplastic resin composite material. ② The mesoporous magnesium oxide also entangles with the polyaniline gel to form a conductive network path, thereby enhancing the conductive performance of the thermoplastic resin composite material.

[0035] (2) The present invention selects a dopant to dope the mesoporous magnesium oxide / polyaniline. The dopant can introduce anions into the polymer chain of the thermoplastic resin to reduce the energy barrier, make electrons migrate more easily, and improve the conductivity of the thermoplastic resin.

[0036] (3) Aminotrimethylphosphonic acid is added to the functional filler. On the one hand, it can form hydrogen bonds with the Mg-O groups on the surface of mesoporous magnesium oxide, which is beneficial to the uniform dispersion of mesoporous magnesium oxide in the thermoplastic resin system. On the other hand, aminotrimethylphosphonic acid has a phosphoric acid group, which can protonate the N atoms on the polyaniline chain, promote the formation of the conductive network structure of the polyaniline gel, and enhance the conductive properties of the thermoplastic resin composite material.

[0037] (4) The present application adds special functional fillers to the thermoplastic resin, which significantly improves the VOC performance and electrical conductivity of the material, wherein the emission of various pollutants is far lower than the standard value, and the surface resistivity of the material is also lower than the resistivity of the composite material using a conventional conductive agent in the comparative example. Therefore, the thermoplastic resin composite material prepared by the present invention meets the requirements for use in automobiles and household appliances, thereby expanding the application field of thermoplastic resin composite materials. DETAILED DESCRIPTION

[0038] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0040] The raw materials used in the following examples are as follows:

[0041] PBT (model 2002U), Polyplastics, Japan;

[0042] PP (model Z30S), Maoming Petrochemical;

[0043] PE (model 5070), Panjin ethylene;

[0044] PA6 (model CM1017), Toray, Japan;

[0045] PS (model 350), Guoqiao, Taiwan Province;

[0046] Sodium oxalate, Hubei Watson Chemical Technology Co., Ltd.;

[0047] Magnesium chloride, Jinan Longjie Chemical Co., Ltd.;

[0048] Deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.;

[0049] Sodium persulfate, Shandong Chuangying Chemical Co., Ltd.;

[0050] Antimony hexafluoride, Wuhan Fengtai Weiyuan Technology Co., Ltd.;

[0051] Acetone, Jinan Wenzhu Chemical Co., Ltd.;

[0052] Aminotrimethylenephosphonic acid, Jinan Rongzheng Chemical Co., Ltd.;

[0053] Aniline, Qingdao Jieshikang Biotechnology Co., Ltd.;

[0054] Conductive carbon black, Shanghai Ximeng Chemical Co., Ltd.;

[0055] Antioxidant (model Irganox168, Irganox1010, Irganox1330), BASF.

[0056] In the following examples, the mixing was performed using a QD-GJS-B12K high-speed mixer, produced by Beijing Hengaode Instruments Co., Ltd.; the twin-screw extruder was a ZSK30 twin-screw extruder, produced by W&P of Germany.

[0057] Preparation Example 1

[0058] (1) Weigh 300 g of sodium oxalate, 280 g of magnesium chloride, 500 g of acetone, and 800 g of deionized water, put them into a reaction vessel, and react them in a 60° C. water bath for 12 h to obtain solution A;

[0059] (2) Filter solution A, wash it, and dry it in a drying oven at 60°C for 10 h to obtain solid B;

[0060] (3) placing solid B in a muffle furnace and calcining at 680° C. for 8 h to obtain mesoporous magnesium oxide;

[0061] (4) Weigh 300 g of mesoporous magnesium oxide, 3 g of initiator sodium persulfate, 1 g of dopant antimony hexafluoride, 400 g of aniline, 300 g of aminotri(methylenephosphonic acid), and 700 g of deionized water, put them into a reaction vessel, and react them in a 70° C. water bath for 10 h to obtain solution C;

[0062] (5) The solution C was filtered, washed, and dried in a drying oven at 50° C. for 40 h to obtain antimony hexafluoride-doped mesoporous magnesium oxide / polyaniline type functional filler M1.

[0063] Example 1

[0064] (1) Weigh 90 parts of PP, 10 parts of functional filler M1, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0065] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material P1.

[0066] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0067] Comparative Example 1

[0068] (1) Weigh 90 parts of PP, 10 parts of conductive carbon black, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0069] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.

[0070] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0071] Comparative Example 2

[0072] (1) Weigh 90 parts of PP, 10 parts of the mesoporous magnesium oxide prepared in step (3) of Preparation Example 1, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0073] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D2.

[0074] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0075] Comparative Example 3

[0076] (1) Weigh 90 parts of PP, 4 parts of the mesoporous magnesium oxide prepared in step (3) of Preparation Example 1, 6 parts of conductive carbon black, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0077] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D3.

[0078] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0079] The PP composite materials prepared in the above Example 1 and Comparative Examples 1-3 were made into test strips by injection molding machine, and the test data are as follows:

[0080] Test items Test Standards unit P1 D1 D2 D3 benzene GB / T 27630 <![CDATA[μg / m 3 ]]> 51 142 68 65 Toluene GB / T 27630 <![CDATA[μg / m 3 ]]> 83 256 98 101 Ethylbenzene GB / T 27630 <![CDATA[μg / m 3 ]]> 65 274 105 99 Xylene GB / T 27630 <![CDATA[μg / m 3 ]]> 95 295 125 118 Styrene GB / T 27630 <![CDATA[μg / m 3 ]]> 38 181 51 49 formaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 36 165 49 50 Acetaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 12 68 28 30 Acrolein GB / T 27630 <![CDATA[μg / m 3 ]]> 6 19 11 10 Surface resistivity GB / T 1410 Ω <![CDATA[3.2×10 6 ]]> <![CDATA[4.8×10 7 ]]> <![CDATA[5.8×10 14 ]]> <![CDATA[3.9×10 7 ]]>

[0081] It can be seen from the above table that, in general, the VOC performance and the conductive performance of Example 1 are better than those of Comparative Examples 1-3.

[0082] Preparation Example 2

[0083] (1) Weigh 400 g of sodium oxalate, 320 g of magnesium chloride, 600 g of acetone, and 1.0 kg of deionized water, put them into a reaction vessel, and react them in a water bath at 80° C. for 16 h to obtain solution A;

[0084] (2) Filter solution A, wash it, and dry it in a drying oven at 80°C for 12 hours to obtain solid B;

[0085] (3) placing solid B in a muffle furnace and calcining at 720° C. for 12 h to obtain mesoporous magnesium oxide;

[0086] (4) Weigh 400 g of mesoporous magnesium oxide, 5 g of initiator sodium persulfate, 3 g of dopant antimony hexafluoride, 480 g of aniline, 500 g of aminotri(methylenephosphonic acid), and 900 g of deionized water, put them into a reaction vessel, and react them in a 90° C. water bath for 16 h to obtain solution C;

[0087] (5) The solution C was filtered, washed, and dried in a drying oven at 70° C. for 48 h to obtain antimony hexafluoride-doped mesoporous magnesium oxide / polyaniline type functional filler M2.

[0088] Example 2

[0089] (1) Weigh 110 parts of PBT, 16 parts of functional filler M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0090] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material P2.

[0091] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0092] Comparative Example 4

[0093] (1) Weigh 110 parts of PBT, 16 parts of conductive carbon black, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;

[0094] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D4.

[0095] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0096] Comparative Example 5

[0097] (1) Weigh 110 parts of PBT, 16 parts of the mesoporous magnesium oxide prepared in step (3) of Preparation Example 2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0098] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D5.

[0099] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0100] Comparative Example 6

[0101] (1) Weigh 110 parts of PBT, 10 parts of the mesoporous magnesium oxide prepared in step (3) of Preparation Example 1, 6 parts of conductive carbon black, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0102] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D6.

[0103] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0104] The PBT composite materials prepared in the above Example 2 and Comparative Examples 4-6 were made into test strips by injection molding machine, and the test data are as follows:

[0105] Test items Test Standards unit P2 D4 D5 D6 benzene GB / T 27630 <![CDATA[μg / m 3 ]]> 56 151 78 81 Toluene GB / T 27630 <![CDATA[μg / m 3 ]]> 91 248 108 111 Ethylbenzene GB / T 27630 <![CDATA[μg / m 3 ]]> 61 268 85 79 Xylene GB / T 27630 <![CDATA[μg / m 3 ]]> 88 288 112 120 Styrene GB / T 27630 <![CDATA[μg / m 3 ]]> 41 179 71 68 formaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 29 158 52 48 Acetaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 16 71 30 32 Acrolein GB / T 27630 <![CDATA[μg / m 3 ]]> 4 17 14 12 Surface resistivity GB / T 1410 Ω <![CDATA[4.5×10 6 ]]> <![CDATA[7.2×10 7 ]]> <![CDATA[6.6×10 7 ]]> <![CDATA[4.2×10 7 ]]>

[0106] It can be seen from the above table that, in general, the VOC performance and the conductive performance of Example 2 are better than those of Comparative Examples 4-6.

[0107] Preparation Example 3

[0108] (1) Weigh 350 g of sodium oxalate, 300 g of magnesium chloride, 550 g of acetone, and 900 g of deionized water, put them into a reaction vessel, and react them in a 70° C. water bath for 14 h to obtain solution A;

[0109] (2) Filter solution A, wash it, and dry it in a drying oven at 70°C for 11 hours to obtain solid B;

[0110] (3) placing solid B in a muffle furnace and calcining at 700° C. for 10 h to obtain mesoporous magnesium oxide;

[0111] (4) 350 g of mesoporous magnesium oxide, 4 g of initiator sodium persulfate, 2 g of dopant antimony hexafluoride, 440 g of aniline, 400 g of aminotri(methylenephosphonic acid), and 800 g of deionized water were weighed and placed in a reaction vessel, and reacted in a water bath at 80° C. for 13 h to obtain solution C;

[0112] (5) The solution C was filtered, washed, and dried in a drying oven at 60° C. for 44 h to obtain antimony hexafluoride-doped mesoporous magnesium oxide / polyaniline type functional filler M3.

[0113] Example 3

[0114] (1) Weigh 100 parts of PE, 13 parts of functional filler M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;

[0115] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material P3.

[0116] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0117] Comparative Example 7

[0118] (1) Weigh 100 parts of PE, 13 parts of conductive carbon black, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;

[0119] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D7.

[0120] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0121] Comparative Example 8

[0122] (1) Weigh 100 parts of PE, 13 parts of the mesoporous magnesium oxide prepared in step (3) of Preparation Example 3, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0123] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D8.

[0124] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0125] Comparative Example 9

[0126] (1) Weigh 100 parts of PE, 10 parts of the mesoporous magnesium oxide prepared in step (3) of Preparation Example 3, 3 parts of conductive carbon black, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0127] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D9.

[0128] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0129] The PE composite materials prepared in the above Example 3 and Comparative Examples 7-9 were made into test strips by injection molding machine, and the test data are as follows:

[0130] Test items Test Standards unit P3 D7 D8 D9 benzene GB / T 27630 <![CDATA[μg / m 3 ]]> 61 168 72 75 Toluene GB / T 27630 <![CDATA[μg / m 3 ]]> 88 231 102 99 Ethylbenzene GB / T 27630 <![CDATA[μg / m 3 ]]> 72 271 98 95 Xylene GB / T 27630 <![CDATA[μg / m 3 ]]> 74 286 89 93 Styrene GB / T 27630 <![CDATA[μg / m 3 ]]> 51 183 73 77 formaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 31 161 56 51 Acetaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 14 68 28 27 Acrolein GB / T 27630 <![CDATA[μg / m 3 ]]> 5 15 11 9 Surface resistivity GB / T 1410 Ω <![CDATA[3.1×10 6 ]]> <![CDATA[6.7×10 7 ]]> <![CDATA[9.2×10 7 ]]> <![CDATA[8.5×10 7 ]]>

[0131] It can be seen from the above table that, in general, the VOC performance and the conductive performance of Example 3 are better than those of Comparative Examples 7-9.

[0132] Preparation Example 4

[0133] (1) Weigh 335 g of sodium oxalate, 295 g of magnesium chloride, 515 g of acetone, and 955 g of deionized water, put them into a reaction vessel, and react them in a 65° C. water bath for 15 h to obtain solution A;

[0134] (2) Filter solution A, wash it, and dry it in a drying oven at 750°C for 11 hours to obtain solid B;

[0135] (3) placing solid B in a muffle furnace and calcining at 6950° C. for 11 h to obtain mesoporous magnesium oxide;

[0136] (4) 335 g of mesoporous magnesium oxide, 4.5 g of initiator sodium persulfate, 2.5 g of dopant antimony hexafluoride, 465 g of aniline, 355 g of aminotri(methylenephosphonic acid), and 865 g of deionized water were weighed and placed in a reaction vessel, and reacted in a water bath at 85° C. for 15 h to obtain solution C;

[0137] (5) The solution C was filtered, washed, and dried in a drying oven at 55° C. for 42 h to obtain antimony hexafluoride-doped mesoporous magnesium oxide / polyaniline type functional filler M4.

[0138] Example 4

[0139] (1) Weigh 85 parts of PA6, 14 parts of functional filler M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0140] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material P4.

[0141] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0142] Comparative Example 10

[0143] (1) Weigh 85 parts of PA6, 14 parts of conductive carbon black, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0144] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D10.

[0145] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0146] Comparative Example 11

[0147] (1) Weigh 85 parts of PA6, 14 parts of the mesoporous magnesium oxide prepared in step (3) of Preparation Example 4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0148] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D11.

[0149] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0150] Comparative Example 11

[0151] (1) Weigh 85 parts of PA6, 8 parts of the mesoporous magnesium oxide prepared in step (3) of Preparation Example 4, 6 parts of conductive carbon black, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0152] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D12.

[0153] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0154] The PA6 composite materials prepared in the above Example 4 and Comparative Examples 10-12 were made into test strips by injection molding machine, and the test data are as follows:

[0155] Test items Test Standards unit P4 D10 D11 D12 benzene GB / T 27630 <![CDATA[μg / m 3 ]]> 66 171 92 95 Toluene GB / T 27630 <![CDATA[μg / m 3 ]]> 82 238 102 99 Ethylbenzene GB / T 27630 <![CDATA[μg / m 3 ]]> 69 262 88 91 Xylene GB / T 27630 <![CDATA[μg / m 3 ]]> 70 281 95 91 Styrene GB / T 27630 <![CDATA[μg / m 3 ]]> 49 187 70 72 formaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 36 155 60 57 Acetaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 12 62 22 25 Acrolein GB / T 27630 <![CDATA[μg / m 3 ]]> 4 17 14 11 Surface resistivity GB / T 1410 Ω <![CDATA[2.8×10 6 ]]> <![CDATA[4.7×10 7 ]]> <![CDATA[7.3×10 7 ]]> <![CDATA[8.5×10 7 ]]>

[0156] It can be seen from the above table that, in general, the VOC performance and the conductive performance of Example 4 are better than those of Comparative Examples 10-12.

[0157] Preparation Example 5

[0158] (1) Weigh 385 g of sodium oxalate, 315 g of magnesium chloride, 575 g of acetone, and 925 g of deionized water, put them into a reaction vessel, and react them in a 75° C. water bath for 15 h to obtain solution A;

[0159] (2) Filter solution A, wash it, and dry it in a drying oven at 68°C for 12 hours to obtain solid B;

[0160] (3) placing solid B in a muffle furnace and calcining at 705° C. for 11 h to obtain mesoporous magnesium oxide;

[0161] (4) Weigh 355 g of mesoporous magnesium oxide, 4.5 g of initiator benzoyl peroxide, 1.5 g of dopant arsenic pentafluoride, aniline, 472 g of aminotri(methylenephosphonic acid), and 385 g of deionized water, put them into a reaction vessel, and react them in a water bath at 85° C. for 14 h to obtain solution C;

[0162] (5) Solution C was filtered, washed, and dried in a drying oven at 66° C. for 41 h to obtain arsenic pentafluoride-doped mesoporous magnesium oxide / polyaniline type functional filler M5.

[0163] Example 5

[0164] (1) Weigh 95 parts of PS, 14 parts of functional filler M5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;

[0165] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material P5.

[0166] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0167] Comparative Example 13

[0168] (1) Weigh 95 parts of PS, 13.5 parts of conductive carbon black, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;

[0169] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D13.

[0170] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0171] Comparative Example 14

[0172] (1) Weigh 95 parts of PS, 13.5 parts of the mesoporous magnesium oxide prepared in step (3) of Preparation Example 5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;

[0173] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D13.

[0174] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0175] Comparative Example 15

[0176] (1) Weigh 95 parts of PS, 9.5 parts of the mesoporous magnesium oxide prepared in step (3) of Preparation Example 5, 4 parts of conductive carbon black, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir evenly to obtain a mixture;

[0177] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D13.

[0178] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0179] The PS composite materials prepared in the above Example 5 and Comparative Examples 13-15 were made into strips by injection molding and tested. The test data are shown in the following table:

[0180] Test items Test Standards unit P5 D13 D14 D15 benzene GB / T 27630 <![CDATA[μg / m 3 ]]> 58 182 85 81 Toluene GB / T 27630 <![CDATA[μg / m 3 ]]> 79 246 91 96 Ethylbenzene GB / T 27630 <![CDATA[μg / m 3 ]]> 58 258 82 77 Xylene GB / T 27630 <![CDATA[μg / m 3 ]]> 92 289 105 109 Styrene GB / T 27630 <![CDATA[μg / m 3 ]]> 56 191 76 71 formaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 49 148 61 62 Acetaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 11 59 18 16 Acrolein GB / T 27630 <![CDATA[μg / m 3 ]]> 8 21 12 11 Surface resistivity GB / T 1410 Ω <![CDATA[2.6×10 6 ]]> <![CDATA[5.4×10 7 ]]> <![CDATA[7.2×10 7 ]]> <![CDATA[3.8×10 7 ]]>

[0181] It can be seen from the above table that the VOC performance and the conductive performance of Example 5 are better than those of Comparative Examples 13-15.

[0182] This shows that the thermoplastic resin composite material prepared by the method provided by the present invention has excellent VOC performance and conductive performance, and can expand the application field of the thermoplastic resin composite material.

[0183] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0184] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A low VOC, high conductivity thermoplastic resin composite material, characterized in that: It is composed of the following components by weight: Thermoplastic resin 90-110 parts Functional filler 10-16 parts Antioxidant 0.1-0.5 parts The functional filler is a doped mesoporous magnesium oxide / polyaniline composite material.

2. The thermoplastic resin composite material according to claim 1, characterized in that: The preparation method of the doped mesoporous magnesium oxide / polyaniline composite material is as follows: (1) placing mesoporous magnesium oxide, an initiator, a dopant, aniline, and aminotri(methylenephosphonic acid) in deionized water and reacting them in a water bath; (2) The reaction solution is filtered, washed and dried to obtain a doped mesoporous magnesium oxide / polyaniline composite material.

3. The thermoplastic resin composite material according to claim 2, characterized in that: The initiator is sodium persulfate, benzoyl peroxide or azobisisobutyronitrile, and the dopant is antimony hexafluoride, arsenic pentafluoride or silicon tetrafluoride.

4. The thermoplastic resin composite material according to claim 2, characterized in that: The mass ratio of the mesoporous magnesium oxide, the initiator, the dopant, the aniline and the aminotri(methylene)phosphonic acid is (30-40): (0.3-0.5): (0.1-0.3): (40-48): (30-50).

5. The thermoplastic resin composite material according to claim 2, characterized in that: The reaction under water bath conditions refers to reacting in a 70-90° C. water bath for 10-16 hours; and drying refers to drying in a 50-70° C. drying oven for 40-48 hours.

6. The thermoplastic resin composite material according to claim 2, characterized in that: The preparation method of the mesoporous magnesium oxide is as follows: (1) adding a magnesium chloride aqueous solution to a sodium oxalate solution and reacting in a water bath; (2) filtering the reaction solution, washing, and drying to obtain a solid substance; (3) The solid material is placed in a muffle furnace and calcined to obtain mesoporous magnesium oxide.

7. The thermoplastic resin composite material according to claim 6, characterized in that: The mass ratio of sodium oxalate to magnesium chloride is (30-40): (28-32); The reaction in a water bath refers to reacting in a water bath at 60-80° C. for 12-16 hours; The drying refers to drying in a drying oven at 60-80° C. for 10-12 hours, and the calcining refers to calcining at 680-720° C. for 8-12 hours.

8. The thermoplastic resin composite material according to claim 1, characterized in that: The antioxidant is one of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene or a mixture of several thereof.

9. The thermoplastic resin composite material according to claim 1, characterized in that: The thermoplastic resin is one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate and polyamide 6.

10. The method for preparing a thermoplastic resin composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Weigh 90-110 parts of thermoplastic resin, 10-16 parts of functional filler, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture; (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.

Citation Information

Cited By

  • High-strength modified aramid nanofiber as well as preparation method and application thereof

    CN120867095A

  • High-strength modified aramid nanofiber, and preparation method and application thereof

    CN120867095B